2021
DOI: 10.1002/ab.22014
|View full text |Cite
|
Sign up to set email alerts
|

The relation between harsh parenting and bullying involvement and the moderating role of child inhibitory control: A population‐based study

Abstract: Harsh parenting has been linked to children's bullying involvement in three distinct roles: perpetrators, targets (of bullying), and perpetrator‐targets. To understand how the same parenting behavior is associated with three different types of bulling involvement, we examined the moderating roles of children's inhibitory control and sex. In addition, we differentiated between mothers’ and fathers’ harsh parenting. We analyzed multi‐informant questionnaire data from 2131 families participating in the Dutch Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
2
11
0
3
Order By: Relevance
“…According to the COR theory, adolescents suffering from harsh parenting are likely to deplete more resources to cope with physical and verbal aggression [ 25 , 26 ], and they have difficulties replenishing resources from the family. This may lead them to generate more negative self-evaluations (e.g., lower self-esteem and self-recognition) and environmental expectations and appraisals (e.g., bullying, low self-control capability [ 53 ]), which increases depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the COR theory, adolescents suffering from harsh parenting are likely to deplete more resources to cope with physical and verbal aggression [ 25 , 26 ], and they have difficulties replenishing resources from the family. This may lead them to generate more negative self-evaluations (e.g., lower self-esteem and self-recognition) and environmental expectations and appraisals (e.g., bullying, low self-control capability [ 53 ]), which increases depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, although we demonstrated the mediating role of depressive symptoms in the relationship between harsh parenting and suicidal ideation, other potential mediating mechanisms may exist. For example, adolescents who experience harsh parenting are more likely to form a low sense of self-worth and be bullied in school due to that low sense of self-worth [ 53 ]. Therefore, harsh parenting may influence adolescents’ suicidal ideation through increased exposure to bullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than different levels of inhibitory control predicting a certain behavioral problem, variations in children's inhibitory control could serve to explain the commonly observed link between environmental influences and behavioral problems (van Dijk et al, 2017). Support for this notion comes from recent research showing that inhibitory control moderates the association between other negative environmental influences and child behaviors (Hogye et al, 2022;Yu et al, 2018). For example, assessing the relationship between harsh parenting and child involvement in bullying, Hogye et al (2022) found that girls who struggle with inhibitory control are more negatively affected by mothers harsh parenting in the sense that they are more likely to act as the perpetrator.…”
Section: Child Characteristics and The Potentially Moderating Role Of...mentioning
confidence: 99%
“…Support for this notion comes from recent research showing that inhibitory control moderates the association between other negative environmental influences and child behaviors (Hogye et al, 2022;Yu et al, 2018). For example, assessing the relationship between harsh parenting and child involvement in bullying, Hogye et al (2022) found that girls who struggle with inhibitory control are more negatively affected by mothers harsh parenting in the sense that they are more likely to act as the perpetrator. Children with low levels of inhibitory control have also been found to be more vulnerable to the implications of physical punishment-as reflected in increased externalizing problems (Yu et al, 2018).…”
Section: Child Characteristics and The Potentially Moderating Role Of...mentioning
confidence: 99%